2019
DOI: 10.1111/ijpp.12542
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of final-year pharmacy students' views on professionalism and ethics in pharmacy practice: an interventional study

Abstract: Objective To evaluate the effects of educational intervention on final‐year pharmacy students' views on professional attitudes and actions required for the present day pharmacy practice. Methods Final‐year pharmacy students (Class 2018) of the largest faculty of pharmacy in north‐east Nigeria were enrolled in this study. Interventional lecture and students small group discussions on situational dilemmas in pharmacy practice, highlighting the application of the Oath of Pharmacist and the Pharmacists' Code of Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Students reported high mean overall professionalism scores and high mean tenet scores across all three professional years, consistent with other studies done in the United Kingdom and Nigeria, where final-year students perceived themselves as having a high level of professionalism (Hanna, Gillen & Hall, 2017;Okoro, 2019). However, in study, not only final-year pharmacy students reported high levels of professionalism but also those in their first and second professional years.…”
Section: Discussionsupporting
confidence: 88%
“…Students reported high mean overall professionalism scores and high mean tenet scores across all three professional years, consistent with other studies done in the United Kingdom and Nigeria, where final-year students perceived themselves as having a high level of professionalism (Hanna, Gillen & Hall, 2017;Okoro, 2019). However, in study, not only final-year pharmacy students reported high levels of professionalism but also those in their first and second professional years.…”
Section: Discussionsupporting
confidence: 88%
“…Educational intervention appeared to positively influence graduates' professional practice. 31,32 However, significant proportion of the participants (37.7%) in this study indicated lack of ethical knowledge as a barrier to discussing ethical issues with customers. This informs the adequacy and teaching approaches of ethics course in our country may be questionable and needs further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…Pharmacy students’ agreement with ‘tenets’ of professionalism was increasingly incorporated into routine assessments to measure educational impact and growth in professional skills over time 35. However, attitudes, values and beliefs proved challenging to measure, and it was unclear how they translate into the professional behaviours that shape society’s perception of and the impact of the pharmacy profession 36 37. This prompted research that described pharmacist professional behaviours that are demonstrated as a result of the individual’s values and beliefs 30 36 37.…”
Section: Introductionmentioning
confidence: 99%
“…However, attitudes, values and beliefs proved challenging to measure, and it was unclear how they translate into the professional behaviours that shape society’s perception of and the impact of the pharmacy profession 36 37. This prompted research that described pharmacist professional behaviours that are demonstrated as a result of the individual’s values and beliefs 30 36 37. These studies typically described behaviours that directly related to pharmacy students’ academic engagement and success (eg, if the student attended class) and how they may translate to workplace behaviours once students are registered pharmacists is uncertain 31 38…”
Section: Introductionmentioning
confidence: 99%